Physioxia Expanded Bone Marrow Derived Mesenchymal Stem Cells Have Improved Cartilage Repair in an Early Osteoarthritic Focal Defect Model - Girish Pattappa; Jonas Krueckel; Ruth Schewior; Dustin Franke; Alexander Mench; Matthias Koch; Johannes Weber; Siegmund Lang; Christian G. Pfeifer; Brian Johnstone; Denitsa Docheva; Volker Alt; et al. (Biology, 2020)
Focal early osteoarthritis (OA) or degenerative lesions account for 60% of treated cartilage defects each year. The current cell-based regenerative treatments have an increased failure rate for treating degenerative lesions compared to traumatic defects. Mesenchymal stem cells (MSCs) are an alternative cell source for treating early OA defects, due to their greater chondrogenic potential, compared to early OA chondrocytes. Low oxygen tension or physioxia has been shown to enhance MSC chondrogenic matrix content and could improve functional outcomes of regenerative therapies. The present investigation sought to develop a focal early OA animal model to evaluate cartilage regeneration and hypothesized that physioxic MSCs improve in vivo cartilage repair in both, post-trauma and focal early OA defects. Using a rabbit model, a focal defect was created, that developed signs of focal early OA after six weeks. MSCs cultured under physioxia had significantly enhanced in vitro MSC chondrogenic GAG content under hyperoxia with or without the presence of interleukin-1β (IL-1β). In both post-traumatic and focal early OA defect models, physioxic MSC treatment demonstrated a significant improvement in cartilage repair score, compared to hyperoxic MSCs and respective control defects. Future investigations will seek to understand whether these results are replicated in large animal models and the underlying mechanisms involved in in vivo cartilage regeneration.